Direito penal mínimo e constituição: o bem jurídico como aquisição evolutiva e a criminalização de seu tempo - Lacerda, Fernando Hideo Iochida (2013)
The scope of the present work is to propose boundaries for the criminalization of our time, from an overview of the juridical value as an evolutionary acquisition. In this sense, the juridical value corresponds to the structural coupling between criminal law and criminal policy, being a product of evolutionary differentiation that operated between the legal and political systems. With that purpose, Niklas Luhmann s theory of systems was adopted as a conceptual assumption, as well as a view of time, considering that we live in a risk society, according to the notions of Ulrich Beck. Applying these scientific references, this thesis proposes a new discussion of the relationship between the Constitution, the juridical value, the criminal law, criminal procedure and criminal policy, defending the idea that it is a function of the legislature to identify the juridical value as a basis for creating criminal law, considering that all the process of penal intervention is positively limited by constitutional norms. The dissertation deals with the criminalization of our time: regarding criminal intervention as a product of politics - analyzing the (non) existence of constitutional warrants binding the production of non constitutional rules, from a vision of the Constitution as a threshold of criminal law, whose foundation would be the juridical value - or concerning the moment of criminal intervention as an operation of the legal system, from the (non) possibility of challenging the constitutional procedural safeguards aiming to adapt risk society's expectations. It is a search for foundations, limits and parameters for the penal system of our time: the minimum criminal law and criminal procedure, informed by constitutional principles